Diagnostic accuracy of ureteroscopic biopsy in predicting stage and grade at final pathology in upper tract urothelial carcinoma: Systematic review and meta-analysis. Issue 11 (November 2020) - Subiela, José Daniel; Territo, Angelo; Mercadé, Asier; Balañà, Josep; Aumatell, Julia; Calderon, Julio; Gallioli, Andrea; González-Padilla, Daniel A.; Gaya, Josep Maria; Palou, Joan; Breda, Alberto
Abstract: Objective: To assess the accuracy of ureteroscopic (URS) biopsies in predicting stage and grade at final pathology in upper tract urothelial carcinoma (UTUC). Materials and methods: The meta-analysis was performed in accordance with the PRISMA statement. Studies providing data on tumor stage and grade at URS biopsy and surgical specimens were included. The negative predictive value (NPV) implies concordance between the absence of subepithelial connective tissue invasion or the presence of low-grade tumors at URS biopsy and the absence of a muscle-invasive disease in the final pathology. Results: A total of 23 studies were included (3547 patients). The stage-to-stage match between URS biopsy/final pathology showed a positive predictive value (PPV) for cT1+/muscle-invasive disease of 94% (95% CI: 84%–100%) and a NPV for cTa-Tis/non-muscle-invasive disease of 60% (95% CI: 52%–68%). The grade-to-grade match between URS biopsy/final pathology was 66% (95% CI: 55%–77%) for low-grade (cLG/pLG) tumors and 97% (95% CI: 94%–98%) for high-grade (cHG/pHG) tumors. The PPV for cHG/muscle-invasive disease was 60% (95% CI: 54%–66%) and the NPV for cLG/non-muscle-invasive disease was 77% (95% CI: 73%–82%). The undergrading and understaging rates were 32% (95%CI: 25%–38%) and 46% (95% CI: 38%–54%), respectively. Conclusions: There is a substantial correlation between tumor grade at URS biopsy and the final pathology. The identification of cHG tumors and subepithelial connective tissue invasion (cT1+) in URS biopsy showed a moderate and a strong correlation with invasive UTUC, respectively. Nevertheless, a certain risk of undergrading and understaging should be assumed. Highlights: ∙ UTUC diagnosis is achieved in most cases through URS biopsy, and a significant proportion of samples can be graded. ∙There is a substantial concordance between tumor grade at URS biopsy and final pathology. ∙cHG tumors and subepithelial connective tissue invasion (cT1+) at URS biopsy have a moderate and strong correlation with invasive UTUC, respectively. ∙URS biopsy shows a certain risk of understaging and undergrading.